Effects of Different Treatments on Seed Germination Improvement of Calotropis persica - Asghar Farajollahi; Bahram Gholinejad; Hamed Jonaidi Jafari (Advances in Agriculture)
The purpose of this study was to investigate the effects of different treatments on seed germination in the desert plant species Calotropis persica (Gand.). This species is known to have long time for seed germination considering arid region condition and short time of access moist. An experiment was performed with 13 treatments and 4 replications in a completely randomized design. Treatments included KNO3 with concentrations of 0.1, 0.2, and 0.3 percent, immersion in hot water for five min, acetylsalicylic acid 100, 200, and 300 mg L−1, ethereal sulfuric acid (60%) for 5 and 10 min, thiourea with concentrations of 0.1% and 0.3%, and prechilling for 10 days. Tap water was used as the control. Our findings indicate that KNO3 0.1% and 100 mg L−1 acetylsalicylic acid were the most effective treatments for improvement of seed germination properties in this species. In a comparison of the two mentioned treatment, KNO3 0.1% treatments is the best.